An Art Therapy Experience with Women with Overweight and Obesity. Gestalt Approach and Art Therapy - Eugenia Beatriz Zalazar (Arteterapia, 2016)
The present article deals with the process and development of application experience of art-therapy with adult women in the context of an interdisciplinary program of behavior change in the treatment of overweight and obesity. In addition they are presented briefly, from different authors, some antecedents and points of relation between the gestalt approach and the art therapy, serving like discussion that contextualizes the experience.